Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1590/s0102-865020190060000006
|View full text |Cite
|
Sign up to set email alerts
|

Pine ( Pinus densiflora ) needle extract could promote the expression of PCNA and Ki-67 after partial hepatectomy in rat

Abstract: Purpose To investigate the effects of pine needle extract (PNE) on the expression of proliferating cell nuclear antigen (PCNA) and Ki-67 during liver regeneration induced by 70% partial hepatectomy (PH) in rat. Methods Forty-eight male rats (SD, 7 weeks) had surgery (70% PH). They were randomly divided into two groups. PH + PNE group was only provided PNE diluted in water (10%) for drinking and PH group was provided water from 5 days before surgery to the time of sacrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As expected, the expression of Ki‐67 increased after treatment with CCl 4 , whereas the administration of GM significantly mitigated the expression of these indicators in HSCs (Figure 2a). PCNA, a cofactor of DNA polymerase, is extensively expressed in the nuclei of proliferating hepatocytes (Lee et al, 2019). We found that PCNA expression was significantly increased in the hepatocytes of rats after treatment with CCl 4 .…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the expression of Ki‐67 increased after treatment with CCl 4 , whereas the administration of GM significantly mitigated the expression of these indicators in HSCs (Figure 2a). PCNA, a cofactor of DNA polymerase, is extensively expressed in the nuclei of proliferating hepatocytes (Lee et al, 2019). We found that PCNA expression was significantly increased in the hepatocytes of rats after treatment with CCl 4 .…”
Section: Resultsmentioning
confidence: 99%
“…We also observed the changes in the number of PCNA-positive cells in the liver and kidney tissues. The changes in PCNA were usually closely related to tissue regeneration (Lee et al 2019). After LPS injection, the PCNA of rat liver and kidney tissues decreased signi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…β-actin was used as loading control. The relative expression level of target protein was expressed as ratio of β-actin [ 64 ].…”
Section: Methodsmentioning
confidence: 99%